L-Phenylalanine methyl ester hydrochloride as a green corrosion inhibitor for mild steel in hydrochloric acid solution and the effect of surfactant additive. Issue 7 (13th January 2016) - Mobin, Mohammad; Zehra, Saman; Aslam, Ruby
Abstract : Structure ofl -phenylalanine methyl ester hydrochloride. Abstract : The inhibitive effect ofl -phenylalanine methyl ester hydrochloride (PMEH) on the corrosion of mild steel (MS) in 1 M HCl solution was investigated at different concentrations and temperatures (30–60 °C) by using weight loss measurements, potentiodynamic polarization measurement, electrochemical impedance spectroscopy (EIS), UV-visible spectrophotometry, and quantum chemical calculations. The obtained results revealed that PMEH is a good inhibitor for the corrosion of MS in HCl solution. The inhibition efficiency (IE) increased with the inhibitor concentration up to 400 ppm as well as with a rise in temperature, which is suggestive of a chemical adsorption mechanism. The adsorption of inhibitor onto the MS surface was found to obey the Langmuir adsorption isotherm. Thermodynamics of adsorption such as enthalpy of adsorption (Δ H ), entropy of adsorption (Δ S ), equilibrium of adsorption ( K ads ), Gibbs free energy (Δ G °), activation and synergism parameters ( S 1 ) were calculated and discussed. Corrosion attack morphologies as observed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) qualitatively verify the results obtained by gravimetric as well as electro-chemical methods. The results obtained from all the techniques are in good agreement.